Analisis Pengaruh Skala Warna dan UV-Vis Terhadap Tingkat Penuaan Isolasi Minyak - Galuh Prawestri Citra Handani; Duanaputri, Rohmanita; Prasojo, Rahman Azis; Wiwaha, Sigit Setya; Akbar , Divac Nabiel; Hastari , Galih Pratiti Citra (Elposys: Jurnal Sistem Kelistrikan, 2023)
A transformer is a static device that can transfer electrical energy using the principle of electromagnetic induction. In operating conditions, the increase of temperature in the transformer will cause the oil insulation having disturbance, which will cause the quality of the insulation to decrease. In this research, oil isolation type shell diala b was chosen which was placed in an accelerated thermal aging chamber experiment device. Then shell diala b oil insulation is heated to a temperature of 120 °C and 160 °C with three sampling times. After this, the oil insulation characteristics were tested which includes oil color scale testing and UV-Visible spectrophotometric testing of the oil. The research method used refers to the IEC 60216-3 2006 standard for aging time and ASTM D-1500 COLOR SCALE for color scale testing. After testing the characteristics of shell diala b oil insulation, it was found that the value of the color scale had increased. Besides that, there has been an increase in the absorption of UV-Visible rays within the oil insulation, which causes the color of the insulation become darker as the temperature and the aging duration in the accelerated thermal aging chamber increases.